Allosterism vs. Orthosterism: Recent Findings and Future Perspectives on A2B AR Physio-Pathological Implications - Barresi, Elisabetta; Martini, Claudia; Da Settimo, Federico; Greco, Giovanni; Taliani, Sabrina; Giacomelli, Chiara; Trincavelli, Maria Letizia (Frontiers in Pharmacology, 2021)
The development of GPCR (G-coupled protein receptor) allosteric modulators has attracted increasing interest in the last decades. The use of allosteric modulators in therapy offers several advantages with respect to orthosteric ones, as they can fine-tune the tissue responses to the endogenous agonist. Since the discovery of the first A1 adenosine receptor (AR) in 1990, several efforts have been made to develop more potent molecules as well as allosteric modulators for AR subtypes. There are four subtypes of AR: A1, A2A, A2B, and A3. Positive allosteric modulators of the A1 AR have been proposed for the cure of pain. A3 positive allosteric modulators are thought to be beneficial during inflammatory processes. More recently, A2A and A2B AR allosteric modulators have also been disclosed. The A2B AR displays the lowest affinity for its endogenous ligand adenosine and is mainly activated as a consequence of tissue damage. The A2B AR activation has been found to play a crucial role in chronic obstructive pulmonary disease, in the protection of the heart from ischemic injury, and in the process of bone formation. In this context, allosteric modulators of the A2B AR may represent pharmacological tools useful to develop new therapeutic agents. Herein, we provide an up-to-date highlight of the recent findings and future perspectives in the field of orthosteric and allosteric A2B AR ligands. Furthermore, we compare the use of orthosteric ligands with positive and negative allosteric modulators for the management of different pathological conditions.